Improving the up/down-conversion luminescence via cationic substitution and dual-functional temperature sensing properties of Er3+ doped double perovskites - Zhu, Jing; Yang, Tongsheng; Li, Hong; Xiang, Yuefei; Song, Ruitong; Zhang, Hongzhi; Wang, Bo (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •The dual-functional temperature sensing is realized through down/up-conversion luminescence.•The emission intensity is optimized via cationic substitution.•ALLT:Er3+ materials have the maximum Sr values of 0.0120/0.0124 K−1 under 379/980 nm excitation, respectively. Er3+ doped phosphors are widely employed as dual-functional optical thermometers owing to their special up/down-conversion luminescence and the thermally coupled energy states (2H11/2 and 4S3/2) of Er3+. Developing Er3+-activated optical thermometers with high performance has been an intriguing topic as well as a significant challenge. Herein, we illustrate the substitution route for alkaline earth ions to obtain the Er3+-activated ALaLiTeO6 (A = Ba, Sr, Ca and Mg) green perovskite phosphors, exhibiting satisfactory temperature sensing properties. Under 379 and 980 nm excitations, the phosphors yield emission peaks at 526, 547 and 660 nm, corresponding to the 2H11/2, 4S3/2 and 4F9/2 → 4I15/2 transitions of Er3+, respectively, among which the 4S3/2 → 4I15/2 transition is the strongest. When cationic substitutions of Ba2+, Sr2+, Ca2+ and Mg2+ are performed, the luminescent intensity is improved significantly and the inner mechanism is clearly revealed. The optical temperature sensing properties of the thermally coupled states are investigated based on the fluorescence intensity ratio principle. Under 379 nm light excitation, SrLaLiTeO6:0.06Er3+ possesses the maximum relative sensitivity of 0.0120 K−1, whereas BaLaLiTeO6:0.06Er3+ possesses the maximum relative sensitivity of 0.0124 K−1 under 980 nm light excitation. Therefore, these materials are the potential candidates for optical thermometer application.